2021
DOI: 10.3389/fonc.2020.585047
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Chaperone TRAP1 as a Candidate Target of Oncotherapy

Abstract: Tumor necrosis factor receptor-associated protein 1 (TRAP1), a member of the heat shock protein 90 (Hsp90) chaperone family, protects cells against oxidative stress and maintains mitochondrial integrity. To date, numerous studies have focused on understanding the relationship between aberrant TRAP1 expression and tumorigenesis. Mitochondrial TRAP1 is a key regulatory factor involved in metabolic reprogramming in tumor cells that favors the metabolic switch of tumor cells toward the Warburg phenotype. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 92 publications
1
23
0
Order By: Relevance
“…Zhang et al [56] report the upregulation of TRAP1 expression in various human malignancies. Its aberrant expression may also lead to the development of cancer [57][58][59][60]. In our study, the expression of CfTRAP1 was low and stable during developmental processes, in adult tissues, and under heat stress.…”
Section: Discussionsupporting
confidence: 47%
“…Zhang et al [56] report the upregulation of TRAP1 expression in various human malignancies. Its aberrant expression may also lead to the development of cancer [57][58][59][60]. In our study, the expression of CfTRAP1 was low and stable during developmental processes, in adult tissues, and under heat stress.…”
Section: Discussionsupporting
confidence: 47%
“…Key signaling protein affected by luteolin and/or oxaliplatin in MFC cells. TRAP1, ERK1/2, and CDC25C are closely related to G 2 /M cell cycle arrest and apoptosis (33,34). Thus, the changes in expression levels of TRAP1, P-ERK1/2/ERK1/2, and CDC25C proteins in MFC cells treated with luteolin and/or oxaliplatin as mentioned before were examined by western blot analysis.…”
Section: Inhibitory Effects Of Luteolin And/or Oxaliplatin On Mfc Cell Viabilitymentioning
confidence: 99%
“…TRAP1 has also been observed to play a role in the regulation of BRAF, subsequently activating the MAPK signaling pathway and inducing the associated metabolic effects described in the BRAF section above [125]. A study on colorectal tumors found a positive correlation between TRAP1 and BRAF levels [42].…”
Section: Trap1-stabilizing Mitochondrial Proteins and Inhibiting Oxidative Phosphorylationmentioning
confidence: 99%
“…Tumor necrosis factor receptor associated protein 1 (TRAP1), an anti-apoptotic mitochondrial protein in the heat shock protein 90 (HSP90) family, is involved in mitochondrial metabolism and known to be altered in cancers. Its regulatory roles in mitochondria include shifting metabolism towards glycolysis, contributing to mitochondrial stability, and combating oxidative stress by lowering ROS [41,[123][124][125]. TRAP1 knockout cells displayed increased oxygen consumption, decreased glycolytic metabolites, increased citric acid cycle metabolites, and increased ROS [126,127].…”
Section: Trap1-stabilizing Mitochondrial Proteins and Inhibiting Oxidative Phosphorylationmentioning
confidence: 99%